Peningkatan Kreativitas Anak melalui Kreasi Balon di Taman Kanak-kanak Pertiwi 1 Kota Padang - Mardiyah, Mardiyah; Nurhafizah, Nurhafizah (JPGI (Jurnal Penelitian Guru Indonesia), 2023)
This study aims to determine the increase in children's creativity through balloon creation. The type of research used is Classroom Action Research (CAR). This classroom action research was conducted in two cycles, namely cycle I and cycle II. In Cycle I the percentage of the average value obtained by students is still low and there is an increase in Cycle II with the average percentage being very high. The results of the percentage of children's values indicate that the Minimum Completion Criteria (KKM) that has been reached has exceeded 75%. Thus it can be concluded that the creativity of children through balloon creation in TK Pertiwi 1 Kota Padang increases, and balloon creations can be used as an alternative to increase the creativity of Early Childhood 5-6 years.